Communication Patterns of Sundanese Ulama to Maintaining Religious Tolerance in West Java: Article in Production (PDF available soon) - Dulwahab, Encep; Muhtadi, Asep Saeful; Enjang; Lestari, Martha Tri (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
West Java is a province that is synonymous with a polite, courteous, and friendly society. Still, ironically, West Java is claimed to be a province that is considered intolerant in matters of communication between religious communities. Even though in West Java there are many religious organizations, there are ulama in various regions, but the label as an intolerant province is challenging to get rid of. This research uses qualitative research with phenomenological theory to determine the da'wah communication by Sundanese ulama in maintaining religious tolerance in West Java. The research results show that the ulama is little involved because the ulama is busy coaching the congregation, solving fiqh problems, and improving the practice of ritual worship. Even if there are ulama who are busy with tolerance activities, this is initiated by the government, which holds various ceremonial activities; the ulama themselves do not have the initiative to keep them. The formal activities most often carried out by the government and ulama include the socialization of Governor Regulations, Laws, guidance, and dialogue between religious communities. There are two types of mass organizations and ulama in implementing ummah harmony, namely mass organizations and ulama, which are strict and firm without compromise. There are mass organizations and ulama who are moderate and love pluralism.